ChemInform Abstract: Chiral Ligands Derived from Monoterpenes: Application in the Synthesis of Optically Pure Secondary Alcohols via Asymmetric Catalysis. Issue 15 (April 2015) - El Alami, Mohammed Samir Ibn; El Amrani, Mohamed Amin; Agbossou‐Niedercorn, Francine; Suisse, Isabelle; Mortreux, Andre
Abstract: Review: [55 refs.